Cathepsins in Rotator Cuff Tendinopathy: Identification in Human Chronic Tears and Temporal Induction in a Rat Model - Seto, Song P. (Ann Biomed Eng, 2015)
While overuse of the supraspinatus tendon is a leading factor in rotator cuff injury, the underlying biochemical changes have not been fully elucidated. In this study, torn human rotator cuff (supraspinatus) tendon tissue was analyzed for the presence of active cathepsin proteases with multiplex cysteine cathepsin zymography. In addition, an overuse injury to supraspinatus tendons was induced through downhill running in an established rat model. Histological analysis demonstrated that structural damage occurred by 8 weeks of overuse compared to control rats in the region of tendon insertion into bone. In both 4- and 8-week overuse groups, via zymography, there was approximately a 180% increase in cathepsin L activity at the insertion region compared to the controls, while no difference was found in the midsubstance area. Additionally, an over 400% increase in cathepsin K activity was observed for the insertion region of the 4-week overused tendons. More cathepsin K and L immunostaining was observed at the insertion region of the overuse groups compared to controls. These results provide important information on a yet unexplored mechanism for tendon degeneration that may operate alone or in conjunction with other proteases to contribute to chronic tendinopathy.